Novel germanium-polyamide6 fibers with negative air ions release and far-infrared radiation as well as antibacterial property. Issue 11 (June 2022) - Chen, Zhi; Ke, Huizhen; Wang, Jian; Li, Yonggui; Jia, Hao; Wei, Qufu
There has been much concern about germanium because of its special atomic nuclear structure to generate negative electrons and far-infrared ray. In this study, novel germanium-polyamide6 fibers were prepared by using micro–nano structured germanium particles as a functional component via melt spinning. The effects of germanium concentration on the morphology, mechanical, negative air ion-releasing, and far-infrared radiation properties of the germanium-polyamide6 fibers were systematically investigated. Besides, the antibacterial activity and mechanism of the fibers against Staphylococcus aureus and Escherichia coli were also discussed. Even though the added germanium particles negatively affected the mechanical performance of the fiber, they were distributed well in the polyamide6 substrate when the concentration was increased from 2% to 6%. Increasing the temperature and pressure induced the germanium-polyamide6 fibers to produce more negative air ions and high far-infrared emissivity. The negative air ion-releasing property of the fiber led to antibacterial performance against S. aureus with more than 99% antibacterial rate. The results confirmed the great application potential of germanium in healthcare, medical, home, and apparel textiles.